Equity-oriented improvement science as organizational resilience: a cross-case comparison of collective thriving - Anderson, Erin; Ringer, James (Frontiers in Education, 2024)
Abstract: This paper explores organizational resilience by applying the theory of social embeddedness of thriving at work from the positive organizational psychology research to schools through a cross-case comparison of five schools involved in improvement work during the pandemic. Using document analysis, observation, and interviews, this study is framed through the literature on workplace stress in schools under pressure and argues that schools with limited resources, such as schools in need of improvement, need to rethink how educators spend time together to improve together if we hope to retain thriving (energetic, motivated, cognitively engaged) educators. The findings focus on collective thriving as demonstrated through the work behaviors embedded in equity-focused improvement in teams (Design Improvement). We explore what collective thriving looks like in two of the five schools, including a discussion of the resources produced from the equity-centered continuous improvement work that supports thriving. Lastly, we provide a comparative analysis of the contextual factors that led to these two schools thriving during this time, as compared to other schools in their cohort. The two schools collectively thrived during the 2020-21 schools year through (a) a systematic approach with common, transparent routines, and (b) inclusive social learning through collective and multiple perspectives.